2012
DOI: 10.3892/ol.2012.949
|View full text |Cite
|
Sign up to set email alerts
|

RhoGDI2 confers resistance to 5-fluorouracil in human gastric cancer cells

Abstract: Abstract. Resistance to 5-fluorouracil (5-FU) in patients with gastric cancer is a serious therapeutic problem and major efforts are underway to understand the underlying mechanisms. We have previously identified RhoGDI2 as a contributor to 5-FU resistance in colon cancer cells using 2D electrophoresis and mass spectrometry and the current study aimed to further investigate this role. The expression of RhoGDI2 in seven gastric cancer cell lines was positively correlated with resistance to 5-FU. Lower 5-FU sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…However, we recently suggested that RhoGDI2 enhances the chemoresistance of gastric cancer through the upregulation of Bcl-2 expression as well as promotes tumor growth and malignant progression. 22 Consistent with our results, Zheng et al suggested that the knockdown of RhoGDI2 expression significantly increases the sensitivity of colon cancer cells to 5-FU [34], and that the ectopic expression of RhoGDI2 in gastric cancer cells induces resistance to 5-FU and reverses 5-FU-induced G2/M phase arrest [35]. …”
Section: Discussionsupporting
confidence: 90%
“…However, we recently suggested that RhoGDI2 enhances the chemoresistance of gastric cancer through the upregulation of Bcl-2 expression as well as promotes tumor growth and malignant progression. 22 Consistent with our results, Zheng et al suggested that the knockdown of RhoGDI2 expression significantly increases the sensitivity of colon cancer cells to 5-FU [34], and that the ectopic expression of RhoGDI2 in gastric cancer cells induces resistance to 5-FU and reverses 5-FU-induced G2/M phase arrest [35]. …”
Section: Discussionsupporting
confidence: 90%
“…There are many reports about the overexpression or downregulation of RhoGDI1 and RhoGDI2 proteins in many types of cancers, with contrasting results [17, 20, 24, 2831], but there is a lack of information about the expression of RhoGDI3 in pancreatic cancer. Thus, to complement the immunofluorescence analysis of RhoGDI3 expression in the pancreatic cell lines, we carried out an immunoblot analysis of total protein extracts using anti-RhoGDI3 antibody, detecting a band of the expected molecular size of 25 kDa, this corresponds to the predicted size for RhoGDI3 (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that RhoGDI2 confers resistance to 5-FU in colon cancer cells. Later on, our and other groups also showed RhoGDI2 play important role in multi-drug resistance in gastric cancer [ 5 - 9 ].…”
Section: Introductionmentioning
confidence: 99%